Práticas, técnicas e geossímbolos da cultura da pesca vernacular na paisagem fluvial do Pitangui-Jotuva - Região dos Campos Gerais (PR) - Scheibel, Carlos Roberto (2013)
This study aims to understand the relationship between anglers and Pitangui River landscape, specifically on its upper part and its right bank tributary, i.e., Jotuva River. The study of vernacular fishing through geographic-ethnographic approach necessarily included the author’s participation as an observing-figure, which enabled him to establish bonds with the territory and go fishing along with the locals, being then able to understand the relationship between the anglers and the river landscape. The products of that relationship - synthesized vernacular fishing into geographical symbols - materialized in artifacts, technical itinerarie, architecture of ranches, camp sites and fishing', as well as the paths connecting fishing spots. Besides reporting the diversity of vernacular fishing practice, the study examines the knowledge body on generative fishing areas, as well as the classification system of local ichthyofauna. The study of geosymbol characterization and knowledge of vernacular fishing pointed to the peculiarity of this sociocultural practice which depends exclusively on rescuing the residents’ memory who have a close connection with the fishing territory, currently threatened by the National Park of Campos Gerais stablishment, as well as other socioeconomic processes that have striken those rural areas.